Pharmacokinetics and Bioequivalence of Two Powders of Azithromycin for Suspension: A Nonblinded, Single-Dose, Randomized, Three-Way Crossover Study in Fed and Fasting States Among Healthy Chinese Volunteers - Junbo Shao; Xingxing Liu; Jing Lin; Jiao Chen; Xiaoyan Xie (Drugs in R&D)
Abstract Background and Objectives Azithromycin, a macrolide antibiotic, is commonly used to treat mild-to-moderate bacterial infections. This research aimed to evaluate the pharmacokinetics (PK) properties and bioequivalence (BE) of two azithromycin (EQ 100 mg base/packet) powders for suspension in Chinese healthy participants in fed and fasting conditions. Methods A total of 90 Chinese healthy participants were enrolled in this nonblinded, single-dose, randomized, semireplicate, three-period, three-sequence, crossover study. Of them, 42 and 40 were categorized to the fed and fasting conditions, respectively. The washout period between doses was 21 days. Blood specimens were harvested prior to administering the drug and 194 h following administration. The plasma levels of azithromycin were analyzed using a validated liquid chromatography–tandem mass spectrometry (LC–MS/MS) approach. PK parameters were measured using noncompartmental analysis. This research compared BE between the reference and test products using the average bioequivalence (ABE) or reference-scaled average bioequivalence (RSABE) method, considering the within-subject variability (S WR) of the reference preparation. Adverse events (AEs) were monitored to examine safety and tolerability. Results The RSABE method (S WR ≥ 0.294) was used to determine the BE of maximal plasma concentration (C max) in both fed and fasting conditions. In the ABE approach, (S WR < 0.294) was adopted to assess the BE of the area under the plasma concentration–time curve from time zero to the last measurable time point (AUC0–t ) and determine the area under the plasma concentration time curve from time zero to time infinity (AUC0–inf). In the fasting condition, the point estimate of the test/reference ratio for C max was 1.08, with a 95% upper confidence bound of − 0.05 < 0.00. The geometric mean ratio (GMRs) for AUC0–t and AUC0–inf was 115.21% [90% confidence interval (CI) 107.25–123.27%] and 113.07% (90% CI 105.14–121.61%), respectively. In the fed condition, the point estimate of the test/reference ratio for C max was 0.94, with a 95% upper confidence bound of − 0.10 < 0.00. The GMR for AUC0–t and AUC0–inf was 99.51% (90% CI of 91.03–108.78%) and 99.43% (90% CI 91.73–107.78%), respectively. These data all satisfied the BE criteria for drugs with high variability. All AEs were transient and mild, and no severe AEs were observed. Conclusions Our study indicated that the test and reference products of azithromycin (EQ 100 mg base/packet) powder for suspension were bioequivalent and safe in healthy Chinese participants, irrespective of the feeding condition. Clinical Trial Registration (chinadrugtrials.org.cn) CTR20232646, registered on 25 August 2023.